Small mammals in the big city - Mazza, Valeria (Doktor); Dammhahn, Melanie (Dr. habil.); Lösche, Elisa; Eccard, Jana (Prof. Dr.) (Global Change Biology, 2020)
A fundamental focus of current ecological and evolutionary research is to illuminate the drivers of animals' success in coping with human-induced rapid environmental change (HIREC). Behavioural adaptations are likely to play a major role in coping with HIREC because behaviour largely determines how individuals interact with their surroundings. A substantial body of research reports behavioural modifications in urban dwellers compared to rural conspecifics. However, it is often unknown whether the observed phenotypic divergence is due to phenotypic plasticity or the product of genetic adaptations. Here, we aimed at investigating (a) whether behavioural differences arise also between rural and urban populations of non-commensal rodents; and (b) whether these differences result from behavioural flexibility or from intrinsic behavioural characteristics, such as genetic or maternal effects. We captured and kept under common environment conditions 42 rural and 52 urban adult common voles (Microtus arvalis) from seven subpopulations along a rural-urban gradient. We investigated individual variation in behavioural responses associated with risk-taking and exploration, in situ at the time of capture in the field and ex situ after 3 months in captivity. Urban dwellers were bolder and more explorative than rural conspecifics at the time of capture in their respective sites (in situ). However, when tested under common environmental conditions ex situ, rural individuals showed little change in their behavioural responses whereas urban individuals altered their behaviour considerably and were consistently shyer and less explorative than when tested in situ. The combination of elevated risk-taking and exploration with high behavioural flexibility might allow urban populations to successfully cope with the challenges of HIREC. Investigating whether the observed differences in behavioural flexibility are adaptive and how they are shaped by additive and interactive effects of genetic make-up and past environmental conditions will ...